(untitled) (Superficies y Vacío, 2021)
Silver nanoparticles AgNPs were synthesized using sodium boronhydride as reductant and poly(ethylendioxithiophene): poly(sodium estiren sulfonate) PEDOT:PSS, as stabilizer. The following synthetic parameters were varied: 1) PEDOT/PSS relative content, using three different commercial formulations; and 2) molar ratio between the silver salt and the reductant. By UV-Vis spectroscopy, the formation of the AgNPs was corroborated with the plasmonic band at 400 nm, moreover changes in the PEDOT absorption were observed with the richer PSS formulations and the salt/reductant ratio was 1, which according to Raman can be associated with a conformational change to a more benzenoid structure. In the other conditions, the spectroscopic properties are similar to those of nanoparticles prepared with only PSS. Based on the results, we consider that the AgNPs are stabilized with the PSS that is in excess, out of the conductive PEDOT:PSS domains, when the formulation contains more PSS or when low amounts of NaBH4 are used. Increasing the NaBH4 content, the AgNPs are formed also inside the PEDOT:PSS domains. The optical and electrical properties of the NPs are thus modulated depending on the preferent stabilization mechanism.